Total Absorption Spectroscopy. (3rd April 2018) - Algora, A.; Rubio, B.; Tain, J. L.
Abstract : Some advances in science come when a new technique is available. There are many examples in the history of science. The advances usually provide the opportunity to see what was hidden to the well-established techniques. It is like employing a lens to see beyond to what is seen to the naked eye.